Ketamine-assisted psychotherapy in adolescents with multiple psychiatric diagnoses - Wolfson, Philip E.; Andries, Julane; Ahlers, Daniel; Whippo, Melissa (Frontiers in Psychiatry, 2023)
Ketamine Assisted Psychotherapy is a new treatment for a variety of mental disorders of adolescence. There is currently an adolescent mental health crisis, with a high prevalence of disorder and many adolescents failing to respond to conventional treatments. While the evidence for the use of ketamine for a variety of treatment refractory mental illnesses in adults is strong, research in adolescents is in its infancy. Ketamine assisted psychotherapy (KAP) has been described in adults with promising results but here we present the first published cases of the use of KAP in adolescents. The four cases include adolescents aged 13-19 at the initiation of treatment, each with a variety of comorbid diagnoses, including treatment resistant depression, bipolar disorder, eating disorders, anxiety, panic, and trauma-related symptoms. They each initially received sublingual ketamine, followed by sessions with intramuscular ketamine. Their courses varied, but in each there were symptomatic and functional improvements, and the treatment was well-tolerated. Subjective patient reports are included. Their courses varied, but in each there were symptomatic and functional improvements, and the treatment was well-tolerated. Subjective patient reports are included. Rapid resolution of symptomatology and suffering is often but not inevitably the result of the application of KAP to adolescent psychiatric care. This development of a new modality can have a singularly positive impact that will expand the psychiatric toolbox and its healing potency.